Cyprus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper assesses Cyprus's export competitiveness and understands factors that could explain export developments, particularly in the services sector. Although Cyprus has been able to leverage its strategic location to diversity its markets for goods exports, as a small island economy, opportunities for diversifying its products mix is more limited. Services exports have performed better in the post-crisis period buoyed by the recovery in Europe and the impact of technological advances on global Information and Communication Technologies-enabled trade. Policies to support greater market diversification, enhance competition and efficiency and strengthen technological adoption would help exports growth. Studies have established the relationship between price and cost competitiveness with trade performance. Cyprus has performed reasonably well with strong service exports over the past few years, aided by improvements in cost competitiveness and a recovery in the European export markets. Policymakers should exploit opportunities brought by the digital transformation while addressing the accompanied risks.